2002
DOI: 10.1248/jhs.48.277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diisononyl Phthalate Migration from Polyvinyl Chloride Products into Human Saliva in Vivo and into Saliva Simulant in Vitro.

Abstract: Human volunteers chewed polyvinyl chloride (PVC) products under controlled conditions for 60 min (four consecutive periods of 15 min), and then the amount of diisononyl phthalate (DINP) migration into the saliva was determined by HPLC. The PVC products consisted of a molded plate containing added DINP (500 mg/g) and five types of commercial toy containing 160-583 mg/g DINP (mean value 372 mg/g). The DINP migration rates ranged from 3.8 to 32.6 µg/cm 2 / hr (mean value 16.4 µg/cm 2 /hr). The DINP contents in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In addition, large amounts of data are di$cult to obtain in vivo for both practical and ethical reasons. Therefore, a simple and reproducible in vitro migration test is required.We found that the results of a 15-min in vitro migration test of DINP from PVC toys by mechanical agitation, especially rotary shaking, were well correlated with the results of in vivo tests over 60 min 14) . We also evaluated the e#ect of experimental conditions on the dialkyl phthalate migration rates into saliva simulant from PVC products using rotary shaking, and we have established a highly reproducible standard procedure.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…In addition, large amounts of data are di$cult to obtain in vivo for both practical and ethical reasons. Therefore, a simple and reproducible in vitro migration test is required.We found that the results of a 15-min in vitro migration test of DINP from PVC toys by mechanical agitation, especially rotary shaking, were well correlated with the results of in vivo tests over 60 min 14) . We also evaluated the e#ect of experimental conditions on the dialkyl phthalate migration rates into saliva simulant from PVC products using rotary shaking, and we have established a highly reproducible standard procedure.…”
mentioning
confidence: 60%
“…The amounts of migration at 30 and 60 min fell below the linear relationship, and it appeared that the migration of DINP would reach saturation eventually. Therefore, we selected an exper- 14) . E#ect of rotation speed: The DINP migration test from plate A into saliva was undertaken at various speeds of rotary shaking (Fig.…”
Section: E#ect Of Experimental Conditions On Dialkyl Phthalatementioning
confidence: 99%
See 2 more Smart Citations
“…• rapid determination of di-2-ethylhexyl phthalate, 332 • quantification of plasticizers 351 • leaching of plasticizers from dialyzers, 333,334 • migration of plasticizer to saliva from PVC products chewed by volunteers, 335 • anionic species formed during PVC degradation analyzed with use of ionic conductivity detector, 336 • stabilizer concentration in PVC, 337 • phenol concentration in PVC, 338 • reverse-phase HPLC use for determination of plasticizer hydrophobicity. 339 Gel permeation chromatography, GPC, is used to determine molecular weight and its distribution.…”
Section: Chromatographic Methodsmentioning
confidence: 99%